Protective Dps–DNA co‐crystallization in stressed cells: an in vitro structural study by small‐angle X‐ray scattering and cryo‐electron tomography. Issue 12 (28th May 2019) - Dadinova, Liubov A.; Chesnokov, Yurii M.; Kamyshinsky, Roman A.; Orlov, Ivan A.; Petoukhov, Maxim V.; Mozhaev, Andrey A.; Soshinskaya, Ekaterina Yu.; Lazarev, Vassili N.; Manuvera, Valentin A.; Orekhov, Anton S.; Vasiliev, Alexander L.; Shtykova, Eleonora V.
Abstract : Under severe or prolonged stress, bacteria produce a nonspecific DNA‐binding protein (Dps), which effectively protects DNA against damaging agents both in vitro and in vivo by forming intracellular biocrystals. The phenomenon of protective crystallization of DNA in living cells has been intensively investigated during the last two decades; however, the results of studies are somewhat contradictory, and up to now, there has been no direct determination of a Dps–DNA crystal structure. Here, we report the in vitro analysis of the vital process of Dps–DNA co‐crystallization using two complementary structural methods: synchrotron small‐angle X‐ray scattering in solution and cryo‐electron tomography. Importantly, for the first time, the DNA in the co‐crystals was visualized, and the lattice parameters of the crystalline Dps–DNA complex were determined. Abstract :